2011
DOI: 10.1007/s11010-011-0986-z
|View full text |Cite
|
Sign up to set email alerts
|

Perifosine as potential anti-cancer agent inhibits proliferation, migration, and tube formation of human umbilical vein endothelial cells

Abstract: Targeting angiogenesis is considered an effective strategy for treating the expansion and metastasis of tumors. The aim of this study is to assess the effects of perifosine, an inhibitor of Akt, on cell proliferation, apoptosis, angiogenesis, and VEGF-induced cell migration in cultured human umbilical vein endothelial cells (HUVECs) in vitro. MTT and cell cycle analysis results indicated that perifosine inhibited the growth of HUVECs in a dose-dependent manner, arrested cell cycle progression at the G(2) phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Both H2009 and H1819 exhibited telomere shortening without a reduction in telomerase activity, suggesting that Perifosine may impair telomere maintenance in some backgrounds in a telomerase enzymatic activity independent manner, such as by regulating telomerase nuclear localization. AKT may modulate telomerase activity through a number of mechanisms, and Perifosine impacts pathways other than AKT, such as the p38 pathway [ 27 ], which may help explain some of the varying telomere biological responses to the drug. It is possible that Perifosine's other activities may be responsible for the observed telomere shortening.…”
Section: Discussionmentioning
confidence: 99%
“…Both H2009 and H1819 exhibited telomere shortening without a reduction in telomerase activity, suggesting that Perifosine may impair telomere maintenance in some backgrounds in a telomerase enzymatic activity independent manner, such as by regulating telomerase nuclear localization. AKT may modulate telomerase activity through a number of mechanisms, and Perifosine impacts pathways other than AKT, such as the p38 pathway [ 27 ], which may help explain some of the varying telomere biological responses to the drug. It is possible that Perifosine's other activities may be responsible for the observed telomere shortening.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have demonstrated that TMV can activate Akt phosphorylation [12] , [39] . Recently, it was reported that the PI3K/Akt pathway affects EC motility and tube formation through the reorganization of actin cytoskeleton [40] , [41] . We for the first time showed that cell motility and tube formation were enhanced via the PI3K/Akt pathway in normal cells by the uptake of TMV.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism for the observed antitumor effect of perifosine in RCC remains unknown. Multiple mechanisms have been implicated that may mediate the antitumor effect of perifosine in preclinical studies, including the induction of apoptosis through both intrinsic and extrinsic pathways, cell cycle arrest, and antiangiogenesis in a variety of tumor types, [13][14][15][16][17][18][19] all of which are mediated through Akt rather than mTOR. The finding that PFS for patients in Groups A and B on the Perifosine 231 trial was nearly identical supports the belief that the mechanism of action of perifosine in RCC is distinct from that of the allosteric mTOR inhibitors.…”
Section: Discussionmentioning
confidence: 99%